Sjællandske træk i Grundtvigs sprog og digtning - Bredsdorff, Morten (Grundtvig-Studier, 1959)
Sealand characteristics in Grundtvig3s language and poetry. By Morten Bredsdorff. Grundtvig was born at Udby, a small village in the southern part of the island Sealand (Sjælland). His poems, hymns and educational ideas have had, as is well known, an immense influence on the whole cultural life of Denmark, and far beyond the borders of this country. None the less he was so deeply rooted in the rural surroundings of his early childhood, that these impressions may be traced all through his elaborate work, crowded as it is with reminiscences of the Sealand dialect, with rural and bucolic metaphors and a certain loquacious use of typical Sealand proverbs and gnomic obsoletes. Although Grundtvig through his education in various parts of his country and his long life in Copenhagen learned to be at home nearly everywhere in Denmark, he was so intimately attached to his native soil in and around Udby, that over and over again he had to revisit this idyllic place. Even as a famous poet and historian he confesses that he can only feel truly at home in southern Sealand. Through quotations from Grundtvig’s poetry and prose it is shown how farreaching and fertile were the impressions and experiences of his early childhood and its immediate surroundings. (The summary translated by the author).